2005
DOI: 10.1055/s-2005-918621
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic Carcinoma Arising from Anterior Skull Base

Abstract: Ameloblastic carcinoma (AC) is an aggressive malignant epithelial odontogenic tumor. It may appear de novo or originate from a pre-existing ameloblastoma or odontogenic cyst. To our knowledge, an AC that originates from the anterior skull base has not been reported before in the English literature. We report a case of an AC that originated from the anterior skull base and invaded the dura of the anterior fossa and discuss its clinical course and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…Two thirds of these tumors arise from the mandible while one third originate in the maxilla. The most common symptom is a rapidly progressing, painful swelling (4,5,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two thirds of these tumors arise from the mandible while one third originate in the maxilla. The most common symptom is a rapidly progressing, painful swelling (4,5,11).…”
Section: Discussionmentioning
confidence: 99%
“…Being a rare disease, there are no treatment guidelines; however, the standard treatment is usually a complete surgical resection with or without radiotherapy (2,11).…”
Section: A B a Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Ameloblastic carcinoma (AC) is an exceptionally rare and aggressive malignant epithelial odontogenic tumor with a poor prognosis that may arise de novo or from malign transformation of a longstanding ameloblastomas (9,13). Two thirds of these tumors arise from the mandible while one third originates from maxilla (12).…”
Section: Introductionmentioning
confidence: 99%
“…2 Ameloblastic carcinoma is a term given to tumours that display histologically malignant features in both primary and metastatic sites with a pattern otherwise resembling ameloblastoma. 2 A review of the literature from 1927 to 2006 revealed 66 cases of ameloblastic carcinoma: 20 cases reported metastases, the majority to the lung; 3 with only 1 case of ameloblastic carcinoma arising from the anterior skull base; 4 1 case of direct extension to the skull base; and 2 case reports, on the same patient, of metastasis to the skull. 5 Review of the literature reveals there is very little written regarding the MRI and 18-fluorodeoxyglucose positron emission tomography-CT (PET-CT) features of ameloblastic carcinoma.…”
Section: Introductionmentioning
confidence: 99%